Lovastatin Inhibits HIV-1-Induced MHC-I Downregulation by Targeting Nef–AP-1 Complex Formation: A New Strategy to Boost Immune Eradication of HIV-1 Infected Cells - Liu, Bingfeng; Zhang, Xu; Zhang, Wanying; Wu, Liyang; Jing, Shuliang; Liu, Weiwei; Xia, Baijin; Zou, Fan; Lu, Lijuan; Ma, Xiancai; He, Dalian; Hu, Qifei; et al. (Frontiers in Immunology, 2019)
Current combined antiretroviral therapy (cART) mainly targets 3 of the 15 HIV proteins leaving many potential viral vulnerabilities unexploited. To purge the HIV-1 latent reservoir, various strategies including “shock and kill” have been developed. A key question is how to restore impaired immune surveillance. HIV-1 protein Nef has long been known to mediate the downregulation of cell-surface MHC-I and assist HIV-1 to evade the immune system. Through high throughput screening of Food and Drug Administration (FDA) approved drugs, we identified lovastatin, a statin drug, to significantly antagonize Nef to downregulate MHC-I, CD4, and SERINC5, and inhibit the intrinsic infectivity of virions. In addition, lovastatin boosted autologous CTLs to eradicate the infected cells and effectively inhibit the subsequent viral rebound in CD4+ T-lymphocytes isolated from HIV-1-infected individuals receiving suppressive cART. Furthermore, we found that lovastatin inhibits Nef-induced MHC-I downregulation by directly binding with Nef and disrupting the Nef–AP-1 complex. These results demonstrate that lovastatin is a promising agent for counteracting Nef-mediated downregulation of MHC-I, CD4, and SERINC5. Lovastatin could potentially be used in the clinic to enhance anti-HIV-1 immune surveillance.